Investigating the potential effect of Holothuria scabra extract on osteogenic differentiation in preosteoblast MC3T3-E1 cells - Sineenart Songkoomkrong; Siriporn Nonkhwao; Supawadee Duangprom; Jirawat Saetan; Sirikul Manochantr; Prasert Sobhon; Napamanee Kornthong; Prateep Amonruttanapun (Scientific Reports)
Abstract The present medical treatments of osteoporosis come with adverse effects. It leads to the exploration of natural products as safer alternative medical prevention and treatment. The sea cucumber, Holothuria scabra, has commercial significance in Asian countries with rising awareness of its properties as a functional food. This study aims to investigate the effects of the inner wall (IW) extract isolated from H. scabra on extracellular matrix maturation, mineralization, and osteogenic signaling pathways on MC3T3-E1 preosteoblasts. The IW showed the expression of several growth factors. Molecular docking revealed that H. scabra BMP2/4 binds specifically to mammal BMP2 type I receptor (BMPR-IA). After osteogenic induction, the viability of cells treated with IW extract was assessed and designated with treatment of 0.1, 0.5, 1, and 5 µg/ml of IW extract for 21 consecutive days. On days 14 and 21, treatments with IW extract at 1 and 5 µg/ml showed increased alkaline phosphatase (ALP) activity and calcium deposit levels in a dose-dependent manner compared to the control group. Moreover, the transcriptomic analysis of total RNA of cells treated with 5 µg/ml of IW extract exhibited upregulation of TGF-β, PI3K/Akt, MAPK, Wnt and PTH signaling pathways at days 14. This study suggests that IW extract from H. scabra exhibits the potential to enhance osteogenic differentiation and mineralization of MC3T3-E1 preosteoblasts through TGF-β, PI3K/Akt, MAPK, Wnt and PTH signaling pathways. Further investigation into the molecular mechanisms underlying the effect of IW extract on osteogenesis is crucial to support its application as a naturally derived supplement for prevention or treatment of osteoporosis.